The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1982
DOI: 10.1093/bja/54.10.1053
|View full text |Cite
|
Sign up to set email alerts
|

Haemodynamic Responses to Induction of Anaesthesia Using Midazolam in Cardiac Surgical Patients

Abstract: The cardiovascular effects of midazolam 0.2 mg kg-1 i.v. were studied during the induction of anaesthesia in 16 premedicated patients subjected to cardiac surgery. In eight patients with coronary artery disease in whom global resting left ventricular function was normal the haemodynamic changes were small and observations on arterial pressure, cardiac index, stroke index, cardiac filling pressures, systemic and pulmonary vascular resistance appeared to parallel those accompanying deep sleep in healthy voluntee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
24
0

Year Published

1983
1983
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(25 citation statements)
references
References 14 publications
1
24
0
Order By: Relevance
“…16 W. HESS et al reported that Midazolam can be used as a valuable alternative to conventional induction agents in cardiac surgical patients without adverse effects on the cardiovascular system. 17 The results we obtained from our study revealed no significant differences in the efficacies of the two drugs and neither caused major alterations in the haemodynamic variables. However, hypotension after induction was observed with Midazolam in few cases which may possibly be due to reduction of sympathetic activity causing vasodilatation and/or interference with the transmembrane influx of Ca 2+ and its enhancement of NO synthesis from endothelial vascular smooth muscles.…”
Section: Discussionmentioning
confidence: 45%
See 1 more Smart Citation
“…16 W. HESS et al reported that Midazolam can be used as a valuable alternative to conventional induction agents in cardiac surgical patients without adverse effects on the cardiovascular system. 17 The results we obtained from our study revealed no significant differences in the efficacies of the two drugs and neither caused major alterations in the haemodynamic variables. However, hypotension after induction was observed with Midazolam in few cases which may possibly be due to reduction of sympathetic activity causing vasodilatation and/or interference with the transmembrane influx of Ca 2+ and its enhancement of NO synthesis from endothelial vascular smooth muscles.…”
Section: Discussionmentioning
confidence: 45%
“…However, hypotension after induction was observed with Midazolam in few cases which may possibly be due to reduction of sympathetic activity causing vasodilatation and/or interference with the transmembrane influx of Ca 2+ and its enhancement of NO synthesis from endothelial vascular smooth muscles. 17,18 Pain on injection and myoclonus were observed only with Etomidate. Miner et al also concluded high incidence of myoclonus (20%) with Etomidate.…”
Section: Discussionmentioning
confidence: 99%
“…Peptic ulceration, intestinal ischaemia and sepsis have all been reported [4][5][6][7], and in patients undergoing operations under cardiopulmonary bypass, local hypoperfusion of the splanchnic region has been found to result in decreased oxygen extraction and to an increase in serum lactate levels [8][9][10]. Induction of general anaesthesia will further augment this redistribution of circulating volume [11].…”
mentioning
confidence: 99%
“…Both SBP and DBP decreased in midazolam group compared to the control and G-CSF groups at the fourhour time point. The difference among the groups may be due to the fact that midazolam can dilate the smooth muscle artery and decrease systematical circulation resistance (16,17). Another reason for this difference is that the depth of anesthesia decreased because of continuous infusion of sodium chloride without any sedation effect, so the BP and HR in the control and G-CSF groups increased after the four-hour time point compared to the midazolam group.…”
Section: Discussionmentioning
confidence: 99%